Leiji Matsumoto : essays on the manga and anime legend - McCarthy, Helen, 1951-; Ashmore, Darren-Jon, 1968-; Poitras, Gilles (Jefferson, N.C. : McFarland & Company, Inc., 2021)
"Leiji Matsumoto is one of Japan's most influential myth creators. Yet the huge scope of his work, spanning past, present and future in a constantly connecting multiverse, is largely unknown outside Japan. Matsumoto was the major creative force on Star Blazers, America's gateway drug for TV anime, and created Captain Harlock, a TV phenomenon in Europe. As well as space operas, he made manga on musicians from Bowie to Tchaikovsky, wrote the manga version of American cowboy show Laramie, and created dozens of girls' comics. He is a respected manga scholar, an expert on Japanese swords, a frustrated engineer and pilot who still wants to be a spaceman in his eighties. This collection of new essays-the first book on Matsumoto in English-covers his seven decades of comic creation, drawing on contemporary scholarship, artistic practice and fan studies to map Matsumoto's vast universe. The contributors-artists, creators, translators and scholars-mirror the range of his work and experience. From the bildungsroman to the importance of textual analysis for costume and performance, from early days in poverty to honors around the world, this volume offers previously unexplored biographical and bibliographic detail from a life story as thrilling as anything he created."--
Includes bibliographical references and index.
Keywords: Matsumoto, Reiji, -- 1938- -- Criticism and interpretation; Comic books, strips, etc. -- Japan -- History and criticism; Cartoonists -- Japan -- Biography; Animated films -- Japan -- Biography